The isotopic and chemical composition of CO2-rich thermal waters in the Mont-Dore region (Massif-Central, France) - Pauwels, Helene; Fouillac, Christian; Goff, Fraser; Vuataz, François (My University, 1997)
Chemical and isotope compositions of fluid samples, collected between 1974 and 1986 from 52 springs or shallow boreholes located in the Mont-Dore region (Massif Central, France), were examined. Some springs and wells were sampled several times during this period. The fluids emerge from Quaternary volcanic rocks or Paleozoic granite at temperatures between 4 and 62 degrees C, and the origin of the H2O is meteoric. The waters can be classified into three groups: bicarbonate fluids, mixed bicarbonate-chloride fluids (with a mineralization up to 8 g/l), and acid-sulfate fluids. Only two fluids contain sufficient Cl- to be considered as 'mature' waters. Previous work has demonstrated that they all contain partly mantle-derived CO2 gas, and that the CO2-rich gas phase and bicarbonate-chloride waters are separated at substantial depth. Mineralized fluids circulate at depth and undergo several processes, such as cooling or dilution with recent freshwater, during their ascent to the surface. Therefore, the CO2-rich gas phase can be partly dissolved in the freshwater, or in deep fluids after their dilution. This process leads to the dissolution of surrounding rocks; such dissolution is discussed on the basis of major-element concentrations (Na, K, Ca, Mg), as well as the Sr 87/86 isotope ratio. Dissolution of S-bearing minerals has also been demonstrated. The presence of the CO2-rich gas phase also leads to isotope exchange between CO2 and H2O. Some mineralized fluids are less affected by these processes than others, in which case they display the chemical and isotopic characteristics of the original deep fluids. It was shown that the applicability of geothermometer calculations for these waters is hampered by several processes that modify the chemical composition. However, some geothermometers can be used for estimating the temperature of the deep fluids using the chemical composition of the less modified fluids. They indicate that fluids emerging from volcanic rocks in the Dordogne valley reach temperatures of around 100- 130 degrees C at depth, while the temperature of the fluid that issues from the granite at Saint-Nectaire is 160-175 degrees C at depth. (C) 1997 Elsevier Science Ltd.
Keywords: MINERAL EQUILIBRIA; GEOTHERMAL WATERS; ROCK INTERACTIONS; LOW-TEMPERATURE; VALLES-CALDERA; NEW-ZEALAND; NEW-MEXICO; CHEMISTRY; ICELAND; SPRINGS